2020
DOI: 10.36079/lamintang.ijeste-0302.107
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Design of Coil Rolling Machines on Robot Solenoids using Macroergonomic Analysis Method and Design (MEAD) and Rapid Entire Body Assesment (REBA) Based on Arduino Microcontroller

Abstract: The making of Indonesian soccer robot in the division of the Indonesian Football Robot Contest (KRSBI) especially in the process of coil rolling machines on a solenoid does not pay attention to ergonomic factors. The process of winding the wire on the solenoid is done using only the hands manually and in an un ergonomic body position, which is turning and bending. As a result, the convolution process lasts longer and in the wrong posture, causing fatigue and back pain. Macroergonomic Analysis and Design (MEAD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…Manufacture Perez, et al [17], Kleiener, et al [2], Muslim, et al [3], Kleiner [6], Wahyuni, et al [18], Pradini, et al [19], Sesariningrum, et al [20], Sukendar, et al [21], Ristyowati [22] Service Industry Murphy, et al [7], Silva [8], Derenevich [9], Nugroho, et al [10], Putra, et al [18], Suzianti, et al [23], Padhil [24], Sumarmi [25] Based on Table 1, it can be concluded that Macroergonomic Analysis and Design (MEAD) framework is widely used both in the manufacturing and service industries. The articles that discuss its application in the manufacturing industry are 53%, while those in the service industry are 47%.…”
Section: Type Of Industry Publicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Manufacture Perez, et al [17], Kleiener, et al [2], Muslim, et al [3], Kleiner [6], Wahyuni, et al [18], Pradini, et al [19], Sesariningrum, et al [20], Sukendar, et al [21], Ristyowati [22] Service Industry Murphy, et al [7], Silva [8], Derenevich [9], Nugroho, et al [10], Putra, et al [18], Suzianti, et al [23], Padhil [24], Sumarmi [25] Based on Table 1, it can be concluded that Macroergonomic Analysis and Design (MEAD) framework is widely used both in the manufacturing and service industries. The articles that discuss its application in the manufacturing industry are 53%, while those in the service industry are 47%.…”
Section: Type Of Industry Publicationmentioning
confidence: 99%
“…Organizational Kleiner, et al [2], Muslim, et al [3], Kleiner [6], Murphy, et al [7], Silva [8], Derenevich [9], Nugroho, et al [10], Perez, et al [17], Putra, et al [18], Pradini, et al [19], Sesariningrum, et al [20], Sukendar, et al [21], Ristyowati [22], Suzianti, et al [23], Padhil [24], Sumarmi [25], Wahyuni, et al [26], Personnel Kleiner, et al [2], Muslim, et al [3], Kleiner [6], Murphy, et al [7], Silva [8], Derenevich [9], Nugroho, et al [10], Perez, et al [17], Putra, et al [18], Pradin, et al [19], Sesariningrum, et al [20], Sukendar, et al [21], Ristyowati [22], Suzianti, et al [23], Padhil [24], Sumarmi [25], Wahyuni, et al [26] Technology Kleiner, et al [2], Murphy, et al [7], Silva [8], Derenevich [9], Nugroho, et al [10], Ristyowati [22], Suzianti, et al [23], Padhil [24], Sumarmi [25] Environment Kleiner, et al [2], Muslim, et al …”
Section: Type Of Industry Publicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 1 show the Arduino UNO board [9], [10]. Adafruit Industries estimated in mid-2011 that over 300,000 official Arduino had been commercially produced, and in 2013, 700,000 official boards were in users' hands.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Misalnya penggunaan teknologi seperti komputer, internet, dan teknologi multimedia yang lain. Menurut Sukendar et al [3], teknologi maklumat dalam konteks pandidikan ialah peralatan teknologi komunikasi atau sistem rangkaian elektronik dan komputer yang boleh digunakan untuk mengumpul, menyimpan, memproses, menyalurkan dan menyampaikan maklumat secara pantas dan tepat. Contoh teknologi maklumat masa kini yang dapat membantu proses PdPc ialah internet dan multimedia.…”
Section: Pendahuluanunclassified